Influence of the Peek Abutments on Mechanical Behavior of the Internal Connections Single Implant - Matos, Jefferson David Melo de [UNESP]; Lopes, Guilherme da Rocha Scalzer [UNESP]; Queiroz, Daher Antonio; Pereira, André Luiz Jesus; Sinhoreti, Mário Alexandre Coelho; Ramos, Nathália de Carvalho [UNESP]; Lino, Vinicius [UNESP]; de Oliveira, Flavio Rosa [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Bottino, Marco Antonio [UNESP] (MDPI, 2022)
The present study aimed to evaluate the biomechanical behavior of PEEK abutments with different heights on single titanium implants. To investigate the implant surface, different tests (scanning electron microscopy, energy-dispersive X-ray, and X-ray diffraction) were adopted. Herein, 20 implants received the 4.5 × 4.0 mm PEEK short abutment (SA) and 20 received the 4.5 × 5.5 mm PEEK long abutment (LA). The abutments were installed using dual-cure resin cement. To determine the fatigue test, two specimens from each group were submitted to the single load fracture test. For this, the samples were submitted to a compressive load of (0.5 mm/min; 30°) in a universal testing machine. For the fatigue test, the samples received 2,000,000 cycles (2 Hz; 30°). The number of cycles and the load test was analyzed by the reliability software SPSS statistics using Kaplan-Meier and Mantel-Cox tests (log-rank) (p < 0.05). The maximum load showed no statistically significant differences (p = 0.189) for the SA group (64.1 kgf) and the LA group (56.5 kgf). The study groups were statistically different regarding the number of cycles (p = 0.022) and fracture strength (p = 0.001). PEEK abutments can be indicated with caution for implant-supported rehabilitation and may be suitable as temporary rehabilitation.
Keywords: bioengineering; dental abutments; dental implants; dental materials; polyetheretherketone